Prilaku Hidup Bersih dan Sehat (PHBS) pada Tatanan Rumah Tangga Masyarakat Desa Kelambir, Kecamatan Pantai Labu - Ridha Panalia Siregar; Mira Ulpayani Harahap; Putra Apriadi Siregar; Muhammad Subhan; Nabila Husna; Muharrammah Isnaini (Universitas Batanghari Jambi, 2023)
The PHBS program in the household is an effort to empower household members to know, be willing and able to practice clean and healthy living behaviors and play an active role in the health movement in the community. PHBS in the household is carried out to achieve a clean and healthy household. The purpose of this study was to analyze the behavior of clean and healthy living in the household structure of the community in Hamlet 1 and Hamlet 2, Kelambir Village, Pantai Labu District. This research is a type of quantitative descriptive research. It was carried out in two hamlets in Kelambir Village, namely Hamlet 1 and Hamlet 2. Data collection was carried out with a research instrument in the form of a questionnaire consisting of questions about PHBS indicators. This study used univariate analysis. From the two hamlets studied, with a sample of 100 households, it can be seen that the indicators that have the highest achievement are indicators of delivery by health workers, using clean water, exclusive breastfeeding, healthy latrines, and weighing toddlers every month.